A comparative study on the coordination of diglycolamide isomers with Nd(iii): extraction, third phase formation, structure, and computational studies. Issue 45 (19th August 2021) - Liu, Yaoyang; Liu, Sheng; Liu, Zhibin; Zhao, Chuang; Li, Chunhui; Zhou, Yu; Jiao, Caishan; Gao, Yang; He, Hui; Zhang, Shaowen
Abstract : The inhomogeneous interactions of M–Oamide in the L II ligand result in differences between the metal-ion extraction performances of two isomeric ligands. Abstract : A novel asymmetric diglycolamide N, N -dimethyl- N ′, N ′-dioctyl diglycolamide (L II ) was synthesized. The Nd(iii ) extraction behavior from HNO3 and loading capability of the solution of L II in 40/60 (v/v)% n -octanol/kerosene were studied. Analyses by the slope method, ESI-MS, and FT-IR indicated that, similar to the previously studied isomer ligand N, N ′-dimethyl- N, N ′-dioctyl diglycolamide (L I ), 1 : 3 Nd(iii )/L II complexes formed. Under the same experimental conditions, the distribution ratio and limiting organic concentration of L II towards Nd(iii ) were smaller than those of L I, but the critical aqueous concentration of L II was larger, which implies that L II exhibited poorer extraction and loading capabilities towards Nd(iii ) than L I, and L II has a tendency to be less likely to form the third phase. The quasi-relativistic density functional theory (DFT) calculation was performed to provide some explanations for the differences in their extraction behaviors. The electrostatic potential of the ligands indicated that the electron-donating ability of the amide O atoms in L II displayed certain differences compared with L I . This inhomogeneity in L II affected the interaction between L II and Nd(iii ), as supported by QTAIM and bonding nature analysis, and it seemed to reflect in the extraction performance towards Nd(iii ).